A nanoparticle vaccine displaying varicella-zoster virus gE antigen induces a superior cellular immune response than a licensed vaccine in mice and non-human primates - Li, Yuanyuan; Tian, Siyu; Ai, Yuanbao; Hu, Zhulong; Ma, Chao; Fu, Meijuan; Xu, Zhenqian; Li, Yan; Liu, Shuyun; Zou, Yongjuan; Zhou, Yu; Jin, Jing (Frontiers in Immunology, 2024)
Herpes zoster (HZ), also known as shingles, remains a significant global health issue and most commonly seen in elderly individuals with an early exposure history to varicella-zoster virus (VZV). Currently, the licensed vaccine Shingrix, which comprises a recombinant VZV glycoprotein E (gE) formulated with a potent adjuvant AS01B, is the most effective shingles vaccine on the market. However, undesired reactogenicity and increasing global demand causing vaccine shortage, prompting the development of novel shingles vaccines. Here, we developed novel vaccine candidates utilising multiple nanoparticle (NP) platforms to display the recombinant gE antigen, formulated in an MF59-biosimilar adjuvant. In naïve mice, all tested NP vaccines induced higher humoral and cellular immune responses than Shingrix, among which, the gEM candidate induced the highest cellular response. In live attenuated VZV (VZV LAV)-primed mouse and rhesus macaque models, the gEM candidate elicited superior cell-mediated immunity (CMI) over Shingrix. Collectively, we demonstrated that NP technology remains a suitable tool for developing shingles vaccine, and the reported gEM construct is a highly promising candidate in the next-generation shingles vaccine development.